2015
DOI: 10.1017/s1431927615000379
|View full text |Cite
|
Sign up to set email alerts
|

Gray-Level Co-Occurrence Matrix Texture Analysis of Breast Tumor Images in Prognosis of Distant Metastasis Risk

Abstract: Owing to exceptional heterogeneity in the outcome of invasive breast cancer it is essential to develop highly accurate prognostic tools for effective therapeutic management. Based on this pressing need, we aimed to improve breast cancer prognosis by exploring the prognostic value of tumor histology image analysis. Patient group (n=78) selection was based on invasive breast cancer diagnosis without systemic treatment with a median follow-up of 147 months. Gray-level co-occurrence matrix texture analysis was per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 36 publications
0
23
0
Order By: Relevance
“…Whereas the prognostic value of malignant cell distribution in breast tumors has been previously established (1416), this is the first investigation of the intensity of their immunostaining for pan-cytokeratin. We found that the mean intensity of immunostaining significantly associated with low-risk.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Whereas the prognostic value of malignant cell distribution in breast tumors has been previously established (1416), this is the first investigation of the intensity of their immunostaining for pan-cytokeratin. We found that the mean intensity of immunostaining significantly associated with low-risk.…”
Section: Discussionmentioning
confidence: 98%
“…Epithelial cells within breast tumors immunostained for pan-cytokeratins have been previously prognostically evaluated using GLCM and binary monofractal algorithms (1416). This study extends the previous reports by undertaking a much wider investigation by utilizing the monofractal, multifractal and intensity analysis of binary and grayscale images of pan-cytokeratin stained malignant cell clusters.…”
Section: Introductionmentioning
confidence: 99%
“…By marking epithelial cells, this kind of staining directs the fractal analysis primarily to the outline of malignant tissue growth patterns, while our analysis was performed on unspecifically stained H&E tissue sections. Furthermore, high tumour grade as an indicator of increased risk also reflected high histomorphological disorder and complexity [18].…”
Section: Discussionmentioning
confidence: 99%
“…The pixel distance was set to 1 and isotropic spatial orientation obtained by averaging the feature values at 0°, 90°, 180° and 270° angles. Five statistical GLCM features were calculated: contrast, correlation, entropy , inverse difference moment ( IDM ) and angular second moment (ASM) by use of the Texture Analyzer plugin by Julio E. Cabrera for Fiji / ImageJ 1.51i according to formulas indicated in our previous report (Vujasinovic et al ., ) and based on the original description (Haralick et al ., ).…”
Section: Methodsmentioning
confidence: 99%